Dampak Penambahan Ragi Tempe terhadap Kualitas Virgin Coconut Oil - Hendrawan, Hendrawan (Ma'soem University, 2025)
Virgin coconut oil, or VCO, is a high-quality oil extracted from fresh coconut flesh without heating or the use of chemicals. This oil is characterized by low water and free fatty acid content, a clear color, a distinctive aroma, and a shelf life of more than 12 months. With advancements in VCO production, fermentation with tempeh yeast as a starter is now possible. This approach has proven effective in maintaining VCO quality, particularly its antioxidant and fatty acid content, as it does not require high temperatures. This research will be conducted in April 2025 at the Chemistry and Processing Laboratory of the Faculty of Agriculture, Ma'soem University. The aim is to measure the impact of tempeh yeast addition on the properties of VCO. The experiment used a Randomized Block Design (RBD) experiment, which included six treatments of tempeh yeast concentrations (0.5%, 0.8%, 1.1%, 1.4%, and 1.7%) with five replications. The results will be statistically analyzed using Analysis of Variance, and if significant differences are found, they will be followed up with Duncan's Multiple Range Test (DMRT) at a 5% significance level. The research findings indicate that tempeh yeast concentration significantly influences VCO quality, as evaluated by water content, fatty acid content, and yield. The higher the tempeh yeast concentration, the better the VCO quality in terms of water content and yield, although the free fatty acid content also increases.